2017
DOI: 10.1071/rd15183
|View full text |Cite
|
Sign up to set email alerts
|

The morphological and functional development of the stria vascularis in miniature pigs

Abstract: The purpose of this study was to examine the morphological and functional development of the lateral wall of the scala media of the cochlea in miniature pigs; light and transmission electron microscopy and electrophysiology were used for this purpose. We showed that the lateral wall of the scala media of the cochlea appears at embryonic Day 21 (E21) when the cochlear duct begins to form. From E28 to E49, the lateral wall can be distinguished according to its position along the cochlea. At E56, cells in the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Our previous studies have found that the size and morphology of pig cochlea are very similar to that of humans. Also similar with humans, the inner ear is essentially fully developed in pigs at birth with normal hearing ability ( Guo et al., 2015a , Guo et al., 2015b ). Compared with rodents which have delayed maturation of their auditory system and require continued inner ear development after birth before gaining normal hearing, the pig, as a large animal model, demonstrates promising prospect of applications in the field of otological research.…”
Section: Pig Deafness Models Share More Similarities To Humans In Botmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have found that the size and morphology of pig cochlea are very similar to that of humans. Also similar with humans, the inner ear is essentially fully developed in pigs at birth with normal hearing ability ( Guo et al., 2015a , Guo et al., 2015b ). Compared with rodents which have delayed maturation of their auditory system and require continued inner ear development after birth before gaining normal hearing, the pig, as a large animal model, demonstrates promising prospect of applications in the field of otological research.…”
Section: Pig Deafness Models Share More Similarities To Humans In Botmentioning
confidence: 99%
“…EUN chemical mutagenesis and spontaneous mutation animal models are useful in finding novel deafness pathogenic genes in animals and equivalent genes in humans. Genetic deafness animal models relate to protein encoding genes, tRNA or rRNA genes and microRNA, etc ( Guo et al., 2015a , Guo et al., 2015b ), encoding transcription factors, ion channels, transporter proteins, extracellular matrix, gap junction proteins, adhesion proteins, myosin, cytoskeletal proteins and microRNAs that regulate target gene expression.…”
Section: Animal Models Have An Irreplaceable Role In Discovering Deafmentioning
confidence: 99%
“…Advantages of using miniature pigs include their relatively light bodyweight, slow rate of growth and overall convenience in experimental operations. They have been used in studies involving tumors, cardiovascular diseases, diabetes, oral surgeries, plastic surgeries, hematologic diseases, genetic and metabolic diseases, and drug safety evaluation ( Guo et al, 2015 ). The miniature pig is now beginning to be applied to inner ear studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies have found that mutations of Mitf in minipigs can lead to a variety of coat color phenotypes, hereditary hearing loss and primary melanoma ( Tachibana et al., 1996 ; Nishimura et al., 2005 ). Considering its proximity with humans in evolution, the minipig becomes an ideal animal model in study human diseases ( Guo et al., 2015a , b ). To establish a suitable animal model for further studies into MITF / Mitf functions, the current study aims to identify alternatively spliced transcript variants of porcine Mitf and analyze their expression in different tissues.…”
Section: Introductionmentioning
confidence: 99%